2013
DOI: 10.1037/a0029616
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the serotonin transporter polymorphism (5-HTTLPR) on empathic and self-conscious emotional reactivity.

Abstract: We examined the relationship between a functional polymorphism of the serotonin transporter (5-HTTLPR) gene and individual differences in emotional reactivity in two laboratory studies. In study 1, empathic responding and physiological reactivity to viewing films of others in distress were assessed in healthy adults in three age groups. In study 2, emotional responding to watching oneself in an embarrassing situation was assessed in healthy adults and in patients with neurodegenerative diseases. In study 1, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 64 publications
6
58
2
3
Order By: Relevance
“…This finding has been contested in some meta-analyses (Munafo, Durrant, Lewis, & Flynt, 2009; Risch, Herrell, Merikangas, et al, 2009), but it has been supported in the most recent and largest meta-analysis (Karg, Burmeister, Shedden, & Sen, 2011). Further, Gyurak et al (2012) found that, when tested experimentally, individuals with two s alleles of the serotonin transporter polymorphism were more emotionally reactive to both pleasant and aversive stimuli than individuals with a long allele.…”
Section: Genetic Markers Hypothesized To Predict Depressive Reactivitmentioning
confidence: 99%
“…This finding has been contested in some meta-analyses (Munafo, Durrant, Lewis, & Flynt, 2009; Risch, Herrell, Merikangas, et al, 2009), but it has been supported in the most recent and largest meta-analysis (Karg, Burmeister, Shedden, & Sen, 2011). Further, Gyurak et al (2012) found that, when tested experimentally, individuals with two s alleles of the serotonin transporter polymorphism were more emotionally reactive to both pleasant and aversive stimuli than individuals with a long allele.…”
Section: Genetic Markers Hypothesized To Predict Depressive Reactivitmentioning
confidence: 99%
“…Finally, the lower-expressing S allele is reported to be associated with greater cortisol stress response in a meta-analysis of association studies [106]. The S allele is also associated with greater personal distress and physiological responses to films of others in distress and more anger, amusement and emotionally expressive behaviours to watching oneself in an embarrassing situation [107]. The association of all of these functional and structural connectivity abnormalities with the serotonin transporter promoter variant indicates how it may be translated into a neurobiologic phenotype that in turn may influence psychopathology and response to stress in adulthood.…”
Section: Downstream Effects Of Impaired Serotonergic Functionmentioning
confidence: 99%
“…Our study was constrained to a single population and a specific developmental stage; however, our results are corroborated by associations between the short allele and heightened sensitivity to social stimuli [13 -16], as well as altered anatomy and functionality in the brain's imitation circuitry [18,19]. Beyond social sensitivity, a vast literature on 5HTTLPR indicates that the short allele is related to diverse phenomena, including: empathy [27], cooperation [28] and dancing [29]. Following Canli & Lesch's [9] suggestion that 5HTTLPR, in interaction with the environment, may influence social behaviour by modulating neural activation in brain regions containing mirror and Von Economo neurons, we note that many seemingly unrelated observations can be reconciled by conceptualization of Both production imitation and social mimicry may contribute to cumulative culture, which arises from highfidelity imitation and social processes including prosociality, group identification and teaching [3,4].…”
Section: Discussionmentioning
confidence: 70%